(4w-9)(5-w)=0

Simple and best practice solution for (4w-9)(5-w)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4w-9)(5-w)=0 equation:


Simplifying
(4w + -9)(5 + -1w) = 0

Reorder the terms:
(-9 + 4w)(5 + -1w) = 0

Multiply (-9 + 4w) * (5 + -1w)
(-9(5 + -1w) + 4w * (5 + -1w)) = 0
((5 * -9 + -1w * -9) + 4w * (5 + -1w)) = 0
((-45 + 9w) + 4w * (5 + -1w)) = 0
(-45 + 9w + (5 * 4w + -1w * 4w)) = 0
(-45 + 9w + (20w + -4w2)) = 0

Combine like terms: 9w + 20w = 29w
(-45 + 29w + -4w2) = 0

Solving
-45 + 29w + -4w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-5 + w)(9 + -4w) = 0

Subproblem 1

Set the factor '(-5 + w)' equal to zero and attempt to solve: Simplifying -5 + w = 0 Solving -5 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + w = 0 + 5 Combine like terms: -5 + 5 = 0 0 + w = 0 + 5 w = 0 + 5 Combine like terms: 0 + 5 = 5 w = 5 Simplifying w = 5

Subproblem 2

Set the factor '(9 + -4w)' equal to zero and attempt to solve: Simplifying 9 + -4w = 0 Solving 9 + -4w = 0 Move all terms containing w to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4w = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4w = 0 + -9 -4w = 0 + -9 Combine like terms: 0 + -9 = -9 -4w = -9 Divide each side by '-4'. w = 2.25 Simplifying w = 2.25

Solution

w = {5, 2.25}

See similar equations:

| 9-3(-2-5)=30 | | 6m-8=2+9m-11 | | 2(z-1)=4(z+5)-10 | | 5(y-7)/4=-2y | | 2.4x=-8.4 | | 3x-5x=20 | | 1/4x-5=-25 | | x^(2/3)-2x^(1/3)-8=0 | | 11-6y-19=7y+8-5y | | 6x+2+3x=9x+2 | | 64/5n-8/9=7/15n | | 11y-5y+6=-24-9y | | 6(7x-3)-4=42x-22 | | n^2-4n-35=0 | | 4y+9=-2y-9 | | 11=8x-8 | | W=1925+-550t | | 2/3d+2/3=8/9 | | (a^8b^4)(-a^2b)= | | 6+2y=7y-2.4 | | -2x+8=-100+7x | | F/5-2.2=-2.5 | | 11+-3x=12-20 | | 2x+3(x-9)=2(x+3) | | 4(8x+9)14y=56 | | 1/6+2y=7y-5/12 | | 2-5x=-14x | | 5n-7=5n-10 | | (2x^3z)(81x^4z^2)(5z)(x^6z^3)= | | -34=3d+8/3 | | (2y-7)(2y-7)=12 | | m-14/a=-27 |

Equations solver categories